Kontekstualisasi Ayat Makkiyah dan Madaniyah Sebagai Solusi Terhadap Isu Kontemporer - Moch Anwar Mambauddin (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2025)
Makkiyah and Madaniyah are not merely classificatory terms used to identify the chronological phases of the Qur’anic revelation in relation to social, cultural, and historical contexts. More importantly, each category embodies distinct values that may serve as normative references for responding to contemporary issues in modern society. This study employs a library research method by collecting data from relevant scholarly literature related to the topic. The data are analyzed through critical reading, systematic documentation, data processing, and descriptive-analytical approaches. The findings reveal three main points. First, the classification of Makkiyah and Madaniyah provides an analytical framework for understanding the socio-historical context of the Prophet Muhammad’s (peace be upon him) prophetic mission. Second, Makkiyah verses function as universal ethical foundations, while Madaniyah verses serve as regulatory and contextual guidelines aimed at revitalizing the Qur’an’s ethical objectives across time. Third, Makkiyah and Madaniyah can be employed as a methodological framework for addressing contemporary issues in a manner that is just, rational, and consistent with the principles of maqāṣid al-syarī‘ah.